Monodisperse macromolecules based on benzodithiophene and diketopyrrolopyrrole with strong NIR absorption and high mobility. Issue 17 (21st December 2015) - Wang, Jiayu; Shi, Keli; Suo, Yue; Lin, Yuze; Yu, Gui; Zhan, Xiaowei
Abstract : A series of monodisperse macromolecules based on benzodithiophene and diketopyrrolopyrrole were designed, theoretically calculated, synthesized and compared, and they exhibited strong NIR absorption and high mobility. Abstract : A series of monodisperse macromolecules with A2 –A1 –D–A1 –A2 structure based on benzodithiophene (BDT) and diketopyrrolopyrrole (DPP) BDT-4DPP, BDT-DPP-Rhod and BDT-DPP-CA were designed, theoretically calculated and synthesized, and compared with their parent molecules BDT-2DPP and BDTS-2DPP with A1 –D–A1 structure. These molecules possessed highly planar molecular geometries and high crystallinity. These molecules exhibited good thermal stability with decomposition temperatures of 322–388 °C, strong visible and near-infrared absorption (500–1000 nm), and HOMO energy levels of −5.38 to −5.19 eV and LUMO energy levels of −3.69 to −3.46 eV. Relative to the parent molecules A1 –D–A1, A2 –A1 –D–A1 –A2 molecules exhibited red-shifted and stronger absorption. The charge transport properties of these molecules were investigated by organic field-effect transistors, and their hole mobilities were 0.036–1.12 cm −2 V −1 s −1 . Replacing alkyl with alkylthio on BDT led to mobility enhancement by one order of magnitude.